Exploring hard and soft domestic ecotourists preferences towards selected eco-friendly attributes of ecolodges in Kinabalu Park, Sabah - Bidin, Sheena; Mariapan, Manohar; Aziz, Azlizam; Ramlan, Mohd Aswad (Universiti Putra Malaysia Press, 2013)
The emergence of the term ecotourism in the 1980`s has brought forward numerous developments in ecotourism industry including the discovery of special niche segments, specifically the `ecotourists`, as well as specialist accommodation type, specifically the `ecolodges`. Although a number of studies have been published with regards to ecotourists` traits and ecolodges guideline, limited information is available on the domestic ecotourists` preferences towards the characteristics that ecolodges embody. Hence, this study is an attempt to address this deficiency by looking at the preferences of two contrasting ecotourist segments, namely, hard and soft domestic ecotourists in Kinabalu Park, a World Heritage Area in Sabah, Malaysia. A discriminant analysis was performed using 403 samples in Kinabalu Park, and it revealed two ecotourist segments with significant differences of preferences towards six constructs of ecolodges. It was also found that hard domestic ecotourists displayed significant differences in preferring eco-friendly attributes as compared to the soft domestic ecotourists on the variables measuring nature based attractions, services and comfort, location and type of accommodation. Soft domestic ecotourists tend to resemble the mass tourists as they placed importance towards services and comfort but disliked being in remote locations. The results of this study demonstrate that ecotourist segments deserve specific considerations by ecotourism managers to cater accommodation packages based on their specific preferences in order to ensure a quality ecotourism experience.